1995
DOI: 10.1021/ie00046a015
|View full text |Cite
|
Sign up to set email alerts
|

Study of Calcium-Based Sorbents for High-Temperature H2S Removal. 2. Kinetics of H2S Sorption by Calcined Limestone

Abstract: Samples of calcined limestone particles having a diameter of about 1 mm were exposed to simulated coal gases containing between 500 and 18 000 ppm H2S for temperatures ranging from 560 to 1100 °C in a differential tube reactor. The formation of CaS was followed quantitatively as well as qualitatively to elucidate the reaction mechanism. Contrary to the limited conversion of CaCOs to CaS, it was found that the limestone particles could be completely converted to CaS by 1% H2S in about 1 h if the particles are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 9 publications
3
44
0
Order By: Relevance
“…The layers were allowed to mix for several minutes at forty times minimum fluidization velocity, but complete mixing was never achieved. (38) The dissociation occurs from the outside surface inward, usually along uniform, concentric areas between the CaCO 3 and the newly formed CaO. Figure 25 illustrates the influence of carbon dioxide concentration and pressure on the dissociation temperature of CaCO 3.…”
Section: Cold Flow Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The layers were allowed to mix for several minutes at forty times minimum fluidization velocity, but complete mixing was never achieved. (38) The dissociation occurs from the outside surface inward, usually along uniform, concentric areas between the CaCO 3 and the newly formed CaO. Figure 25 illustrates the influence of carbon dioxide concentration and pressure on the dissociation temperature of CaCO 3.…”
Section: Cold Flow Model Resultsmentioning
confidence: 99%
“…Fenouil [36][37][38] Borgwardt [40] determined that the combined effects of H 2 O and CO 2 on the sintering of CaO at a given temperature were greater than the summative effect of each gas alone, and surface area loss was more strongly affected than porosity. It was determined that grain boundary and surface diffusion mechanisms were responsible.…”
Section: Cold Flow Model Resultsmentioning
confidence: 99%
“…21 The X 12 Y 12 cages have been extensively investigated to assess their applications as adsorbent for different analytes. In our recent works, 26,[29][30][31]35,36 44,45 Low activation energy of 21.59 kJ/mol was obtained for these reactions via thermogravimetric analysis. 6 Furthermore, the heat of adsorption amounts to 81 ± 22 kJ/mol, indicating that the adsorption of H 2 S on CaO belongs to the category of entropically ideal site adsorption.…”
Section: Funding Information Iran Nanotechnology Initiative Councilmentioning
confidence: 99%
“…CaO has also received considerable interest in fundamental research because of its wide availability in natural minerals. The kinetics of the reactions between H 2 S and calcined limestone (CaO + H 2 S → CaS + H 2 O) have been experimentally examined . Low activation energy of 21.59 kJ/mol was obtained for these reactions via thermogravimetric analysis .…”
Section: Introductionmentioning
confidence: 99%
“…From their results the authors suggested that Model 2 best describes the kinetics of both reactions. Fernouil and Lynn (1995b) also studied the kinetics of the reaction between calcined limestone and H2S gas. In their work 20 -30 mg of 1.75 mm limestone particles were used.…”
Section: Sulfidation With Cosmentioning
confidence: 99%